HERPES ASSOCIATED ERITHEMA MULTIFORME (HAEM ) ON THE PSYCHOSOMATIC PATIENT : A CASE REPORT - Yayun Siti Rochmah; Rochman Mujayanto (Jurnal Medali, 2021)
Background : Erythema multiforme is an acute mucocutaneous inflammation which is self limiting desease. One of caused of Erythema multiforme is Herpes Simplex Virus infection diagnosed as Herpes Associated Erytema Multiforme (HAEM). The psychosomatic patients should be wary of anti-depressant therapy, because if there is an allergy, it can trigger the occurrence of erthema multiformis. In this paper, we will reported HAEM case on psychosomatic patient.Case and management : A case of 23 years old female patient with chief complaint sore and pain lips since one weeks ago. The patient has been on anti-depressant therapy for one month. Clinical examination on patient showed that there were erosive lesion covered by reddish brown crusta, sloughing on the border between lips and labial mucosa, and bloody lips. The results of laboratory tests show positive HSV. Patient was diagnosed with HAEM. Therapy given to the patient was corticosteroid topical oitment, acyclovir and oral rinse antiseptics. After two weeks the administration, condition on the patient has improved.Conclusions : HAEM cases if treated properly can recover well. Trigger factors must be controlled so that not recurrance